Evolution of structure and residual stress of a fcc/hex-AlCrN multi-layered system upon thermal loading revealed by cross-sectional X-ray nano-diffraction. (1st January 2019) - Jäger, N.; Klima, S.; Hruby, H.; Julin, J.; Burghammer, M.; Keckes, J.F.; Mitterer, C.; Daniel, R.
Abstract: Understanding the influence of process conditions and coating architecture on the microstructure and residual stress state of multi-layered coatings is essential for the development of novel thermally and mechanically stable coatings and requires advanced depth resolving characterization techniques. In this work, an arc-evaporated multi-layered coating, consisting of alternating Al70 Cr30 N and Al90 Cr10 N sublayers with an individual layer thickness between 120 nm and 380 nm, was investigated. The as-deposited state of the multi-layered coating and the state after vacuum annealing at 1000°C for 30 min was studied along its cross-section by synchrotron X-ray nano-diffraction using a beam with a diameter of 50 nm. The results revealed sublayers with alternating cubic and hexagonal phase, causing repeated interruption of the grain growth at the interfaces. The in-plane residual stress depth distribution across the coating thickness could be tuned in a wide range between pronounced compressive and slight tensile stress by combining the effects of the coating architecture and the modulated incident particle energy controlled by the substrate bias voltage ranging from −30 V to −250 V. This resulted in an oscillatory stress profile fluctuating between −2 GPa and −4.5 GPa or pronounced stress gradients with values between −4 GPa and 0.5 GPa. Finally, the decomposition routes of the metastable cubic Al70 Cr30 N phase could be controlled by the Al90 Cr10 N sublayers which acted as nucleation sites and governed the texture of the decomposition products as Cr2 N. The results demonstrate that the cross sectional combinatorial approach, relying on a sophisticated multi-layer architecture combining various materials synthesized under tailored conditions, allowed for resolving structural variations and stress profiles in the individual layers within the complex architecture and pioneers the path for knowledge-based development of multi-layered coatings with predefined microstructure and a dedicated stress design. Graphical abstract: Image 1